Evoluç\~ao e determinantes da taxa de homicídios no Brasil - Adolfo Sachsida; Mario Jorge Cardoso de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The main objective of this article is to verify the impact of both the incarceration rate and the number of police officers over the homicide rates. Overall, our results suggest that the increase in both the incarceration rate and the number of police officers are important do deter homicides. That is, the successful fight against crime can be achieved by incarceration and police officers independently of what happens with other socioeconomic variables.
Keywords: K42; Z18; C23; 330; criminality; homicide; incarceration rate; number of police officers